Protection of Persons with Disabilities in Armed Conflict in Gaza through the Application of the Distinction Principle - Aprisal, Jelita Septiani; Supriyanto, Agustinus; Alhaj, Samar T.M. (Kosmik Hukum, 2025)
Protection for people with disabilities during armed conflict in Gaza must prioritize the application of the Distinction Principle in international humanitarian law. The Distinction Principle ensures that military attacks are directed only at legitimate military targets, not at civilians, including those with disabilities. Therefore, it is crucial to examine how protection for people with disabilities in Gaza with the application of this principle can be enhanced, and discuss the prospects of regulations governing this issue in the future. The research method employed is normative legal research, utilizing both statutory approach related to the issue and conceptual approach focusing on the Distinction Principle. People with disabilities in Gaza face significant challenges in accessing healthcare, evacuation, and humanitarian aid. Consistent and stringent implementation of the Distinction Principle is essential to ensure their protection from the adverse effects of war. Concrete steps such as improving military training, monitoring violations, and enforcing these principles are necessary to strengthen their protection. Overall, protection for people with disabilities in Gaza is a global humanitarian responsibility that requires collective commitment to ensure compliance with international law and improve the living conditions of people with disabilities amidst armed conflict.